Information Systems Architecture and Technology: Proceedings of 36th International Conference on Information Systems Architecture and Technology - ISAT 2015 - Part II - Grzech, Adam.; Borzemski, Leszek; Świątek, Jerzy; Wilimowska, Zofia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This four volume set of books constitutes the proceedings of the 36th International Conference Information Systems Architecture and Technology 2015, or ISAT 2015 for short, held on September 20-22, 2015 in Karpacz, Poland. The conference was organized by the Computer Science and Management Systems Departments, Faculty of Computer Science and Management, Wroclaw University of Technology, Poland. The papers included in the proceedings have been subject to a thorough review process by highly qualified peer reviewers. The accepted papers have been grouped into four parts: Part I-addressing topics including, but not limited to, systems analysis and modeling, methods for managing complex planning environment and insights from Big Data research projects. Part II-discoursing about topics including, but not limited to, Web systems, computer networks, distributed computing, and multi-agent systems and Internet of Things. Part III-discussing topics including, but not limited to, mobile and Service Oriented Architecture systems, high performance computing, cloud computing, knowledge discovery, data mining and knowledge based management. Part IV-dealing with topics including, but not limited to, finance, logistics and market problems, and artificial intelligence methods.
Web Systems -- Computer Networks and Distributed Computing -- Multi-Agent and IoT Systems.
Keywords: Telecommunication; Computer networks .; Business information services; Communications Engineering, Networks; Computer Communication Networks; Business Information Systems